Synthesis, characterization and thermodynamic properties of poly(3-mesityl-2-hydroxypropyl methacrylate-co-N-vinyl-2-pyrrolidone) - Açikses, A; Kaya, I; Sezek, Ü; Kirilmis, C (Elsevier Sci Ltd, 2005)
Poly(3-mesityl-2-hydroxypropyl methacrylate-co-N-vinyl-2-pyrrolidone) P(MHPMA-co-VP) was synthesized in 1, 4-dioxane solution using benzoyl peroxide (BPO) as initiator at 60 degrees C. The copolymer was characterized by H-1 C-13 NMR, FT-IR, DSC, TGA, size exclusion chromatography analysis (SEC) and elemental analysis techniques. According to SEC, the number-average molecular weight (M-n), weight-average molecular weight (M-w) and polydispersity index (PDI) values of PMHPMA-co-VP were found to be 58,000, 48 1,000 g/mol and 8.26, respectively. According to TGA, carbonaceous residue value of PMHPMA-co-VP was found to be 6% at 500 degrees C. Also, some thermodynamic properties of PMHPMA-co-VP such as the adsorption enthalpy, Delta H-a, molar evaporation enthalpy, Delta H-v the sorption enthalpy, Delta H-1(s) sorption free energy, Delta G(1)(s), sorption entropy, Delta S-1(s), the partial molar free energy, Delta G(1)(infinity), the partial molar heat of mixing, Delta H-1(infinity), at infinite dilution was determined for the interactions of PMHPMA-co-VP with selected alcohols and alkanes by inverse gas chromatography (IGC) method in the temperature range of 323-463 K. According to the specific retention volumes, chi(infinity)(12) the weight fraction activity coefficients of solute probes at infinite dilution, Omega(infinity)(1) and Flory-Huggins interaction parameters, chi(infinity)(12) between PMHPMA-co-VP-solvents were determined in 413-453 K. According to Q, and chi(infinity)(12), selected alcohols and alkanes were found to be non-solvent for PMHPMA-co-VP at 413-453 K. The glass transition temperature, T-g, of the PMHPMA-co-VP found to be 370 and 363 K, respectively, by IGC and DSC techniques, respectively. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: poly(3-mesityl-2-hydroxypropyl methacrylate-co-N-vinyl-2-pyrrolidone); synthesis and characterization; inverse gas chromatography